Usefulness of upright T wave in lead aVR for predicting short-term prognosis of patients with ischemic stroke - Hong-Jie Yang (KeAi Communications Co., Ltd., 2018)
Background: Upright T wave in lead aVR (TaVR) has recently been reported to be associated with cardiovascular death and mortality in general population and in patients with prior cardiovascular disease (CVD). However, the evidence for the predictive ability of TaVR in patients with ischemic stroke (IS) is lacking. Methods: A total of 625 consecutive patients with IS (mean age: 66 ± 12 years; 379 male) were enrolled in this study between January 2013 and December 2014. Patients were divided into upright TaVR (≥0 mV; n = 201) and negative TaVR (<0 mV; n = 424) groups. All patients were evaluated with respect to clinical features and in-hospital clinical results. Results: Overall, the prevalence of upright TaVR was 32.2% at baseline. Patients with an upright TaVR were older, had a higher percentage of CVD and hypertension, higher level of MB isoenzyme of creatine kinase (CKMB), faster heart rate, higher rate of QT prolongation > 450 ms, higher rate of negative T in lead II, higher rate of negative T in lead V6, higher rate of ST depression, and longer QTc duration. During the mean follow-up period of 20.0 ± 5.8 months, 29 (4.6%) patients experienced all-cause death and 12 (1.9%) patients experienced cardiovascular death, the primary end point. Concomitantly, 94 (15%) patients experienced recurrence of IS, the secondary end point. After adjusting for clinical covariates, upright TaVR was independently associated with all-cause death [hazard ratio (HR): 2.88, 95% confidence intervals (CI): 1.07–7.73], cardiovascular death (HR: 3.04, 95% CI: 1.07–8.64), and IS recurrence (HR: 1.86, 95% CI: 1.08–3.20). Conclusions: Upright TaVR in patients with IS is associated with increased mortality and recurrence of IS. Keywords: T wave in lead aVR, Ischemic stroke, Prognosis